Heat and Cold Shocks Decrease the Incidence of Diapause in Trichogramma telengai Larvae - Natalia D. Voinovich; Sergey Y. Reznik (Insects)
Insect diapause and response to thermal stress are similar in the variety of manifestations. However, the influence of thermal shocks on the incidence of insect diapause has not been sufficiently studied. Our laboratory experiments showed that both cold (−10 °C) and heat (43 °C) shocks experienced for at least 20–30 min significantly reduced the incidence of facultative larval winter diapause in the insect egg parasitoid Trichogramma telengai. However, the patterns of these responses were substantially different. In particular, the peaks of the sensitivity to diapause-averting effects of heat and of cold shocks fell, correspondingly, on middle-stage (5 days of development at 15 °C) and late-stage (9–11 days of development at 15 °C) larvae. Heat shocks influence the incidence of diapause mostly via the changes in the initial proportions of diapause-destined and non-diapause-destined individuals, whereas the effect of cold shocks is mostly based on differential mortality (i.e., the difference in mortality among treatments of the same experiment) with better survival of non-diapause-destined individuals. These results elucidate the peculiarities of the interaction between stress and diapause, allowing us to specify the methods for Trichogramma mass rearing and storage.